Carnitine Deficiency after Long-Term Continuous Renal Replacement Therapy - Caroline Van de Wyngaert; Joseph P. Dewulf; Christine Collienne; Pierre-François Laterre; Philippe Hantson (Case Reports in Critical Care)
A 60-year-old man was admitted in the intensive care unit (ICU) for a rapidly progressive respiratory failure due to SARS-CoV-2 infection. He developed numerous complications including acute kidney injury (AKI) requiring prolonged continuous renal replacement therapy (CRRT). Enteral feeding was initiated on day 8. Despite nutritional management, there was a remarkable amyotrophy and weight loss. On day 85 in the ICU, the patient became progressively unresponsive. An extensive metabolic workup was performed, and blood results showed hyperammoniemia and hypertriglyceridemia. Plasma free carnitine level was low, as was also copper. After carnitine supplementation, the neurological condition rapidly improved, and metabolic perturbations regressed. Prolonged CRRT may be complicated by clinically significant deficiency in micronutrients and trace elements.